TRANSPARANSI KONTRAK, KEPATUHAN SYARIAH, DAN BANTUAN BISNIS SEBAGAI PENDORONG KEPUASAN WIRAUSAHA MIKRO DI PERBANKAN ISLAM INDONESIA - Budi Sukardi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the impact of integrating contract transparency, authentic Sharia compliance, and business assistance programs on the satisfaction levels of micro-entrepreneurs in the Indonesian Sharia banking sector. Utilizing a deep thematic library research method, this analysis synthesizes empirical data from banking performance reports and literature to evaluate the effectiveness of services for the micro-sector. The research results indicate that contract transparency significantly reduces information asymmetry, while Sharia compliance acts as an ethical filter that builds spiritual loyalty. Business assistance programs, particularly those integrating Islamic leadership values, are proven to be catalysts for scaling up micro-enterprises. The synergy of these three factors, supported by fintech and blockchain innovations, creates a sustainable financial inclusion model. The implications of this study emphasize the importance for Sharia financial institutions to shift from being mere capital providers to strategic partners in developing an inclusive and equitable national halal ecosystem.